OA'ANA CAVE OPTIMIZATION AS A NEW AND POTENTIAL LOCAL TOURISM DESTINATION AS PART OF COMMUNITY EMPOWERMENT IN KUANHEUN VILLAGE - WEST KUPANG, NTT - Adrianus P. Wangge; Sheryl M. Lena Bengu; Leonardus A. Klau; Alfonso W. Resi Reo; Haru A. P. Oembu Rey; Anselmus A. Atasoge; Maria S. Uakleo; Valerianus Korsin; Elisa N. Seran; Antonia H. Ola; Erina S. Loasana; Marianus Banase; Yeremias Sesnae; Yohanes Adonis; Bernadinus Meo Roga; Aplonia Nelci Ke Lomi (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Higher Education students through students’ community service actively participate in the development of a village through mentoring, empowering, and raising community awareness of the area's potential. Kuanheun Village located in West Kupang District, Kupang Regency, East Nusa Tenggara. Kuanheun Community is a village with natural potential for tourism development. However, there are still tourist attractions that are isolated and unknown to visitors, for instance, the Oa'ana Cave (small water cave). Students from Widya Mandira Catholic University in Community Empowerment Program worked hard to build Kuanheun's tourist village: tourist site, replanting surrounding tourist sites, designing Oa’ana Cave (small water cave) tourist attractions, and optimizing the use of social media as an information and promotion medium. Thus, numerous KKN work initiatives can assist promote Kuanheun Village's tourism potential.